Mapping Social Cognition Research in Social Sciences: A Bibliometric Study towards Achieving the Sustainable Development Goals (SDGs) - Ardhita Eko Ginanjar; Juwinda Lusi Apriliani; Nabila Arum Callista Bakti; Abdullah Azzam Robbani (Sekolah Tinggi Agama Islam Sabilul Muttaqin Mojokerto, 2025)
Objective: One of the fundamental urgencies of the SDGs and the starting point is the psychology and mental state of humans to realize good quality resources. This research aims to analyze the scientific trends regarding social cognition in social science conceptually, knowledgeably, and socially over the last decade in order to obtain the latest developments that have not been previously conducted. Method: This research employs a bibliometric approach through Rstudio Biblioshiny to illustrate scientific research data accessed through the Scopus database within the span of 2014-2024. Results: There is a positive overall trend in social cognition in social science, although there has been a downward trend since 2021. Based on the theory of mind, the development of the theme focuses on the psychological relationship between humans and technology. Novelty: The use of the latest year data and the contextualization of social cognition in social science represents a novelty in this research. This offers contributions for further researchers and policymakers to conduct collaborative research on topic development and monitoring.